2011
DOI: 10.3109/00498254.2011.564332
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite identification by mass spectrometry: forty years of evolution

Abstract: When the Drug Metabolism Discussion Group was instigated in 1971, metabolite identification by mass spectrometry was a slow and laborious process undertaken by mass spectrometrists who seemed to continually disappoint their colleagues by failing to obtain the metabolite spectra. This was usually because not enough material was supplied or the material was impure. Today, accurate metabolite information can be obtained rapidly with little material by utilizing a range of mass spectrometers with complementary pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 99 publications
0
10
0
1
Order By: Relevance
“…In the last few years, several mixtures of phenolics have been analyzed with advanced LC-MS/MS equipment [17,18,19,20,21] including various publications dealing with the on-line HPLC-MS detection of flavonoids, phenolic acids and alkaloids in citrus fruits [12,13,14,15,22,23]. The advantage of HPLC-MS is its sensitivity and selectivity, and the ability to use tandem mass spectrometry for the observation of aglycones and diagnostic fragments [17,18]. As a continuation of our studies on antioxidant activity and phenolic composition of Chilean fruits [24,25], in the present work we have analyzed for the first time peels and edible pulps from three citrus varieties (pica, sutil and genova), highly consumed in northern Chile, for phenolic compounds using HPLC-UV-MS and compared their vitamin C content and antioxidant capacities.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, several mixtures of phenolics have been analyzed with advanced LC-MS/MS equipment [17,18,19,20,21] including various publications dealing with the on-line HPLC-MS detection of flavonoids, phenolic acids and alkaloids in citrus fruits [12,13,14,15,22,23]. The advantage of HPLC-MS is its sensitivity and selectivity, and the ability to use tandem mass spectrometry for the observation of aglycones and diagnostic fragments [17,18]. As a continuation of our studies on antioxidant activity and phenolic composition of Chilean fruits [24,25], in the present work we have analyzed for the first time peels and edible pulps from three citrus varieties (pica, sutil and genova), highly consumed in northern Chile, for phenolic compounds using HPLC-UV-MS and compared their vitamin C content and antioxidant capacities.…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols are some of principal compounds related to the benefits of fruits, vegetables, wine and plant tea consumed in the diet, due to their antioxidant properties. Plant phenolics are also useful as chemotaxonomic markers [1,2]. The polyphenols are recognized for their nutritional value, since they may help reduce the risk of chronic disease and have a positive effect on health [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the response in ESI-MS differed by factor 25 for two oxidative isomeric metabolites with same chemical formula [43] or that no signal in contrary to parent drug has been observed for metabolite in positive ionization ESI. Detection of metabolite was in this case possible only in negative ionization mode [26]. However, with the commonly and easily used UV detection, the metabolites have often the same chromophore as the parent drug (but not always [40], hence giving similar response.…”
Section: Direct Quantificationmentioning
confidence: 99%
“…A short overview of analytical strategies for identification of metabolites will be provided. More information regarding metabolite identification can be found in following review articles [7,[23][24][25][26][27]. The selection of suitable LC-MS instrumentation is needed for qualitative evaluation of metabolites.…”
Section: Qualitative Evaluation Of Metabolitesmentioning
confidence: 99%